Interaction Between Group Discussions and Video-Based Learning About Students' Achievements in Learning English - Ilmiya, Sulis Janu Hartati, Sunardjo (Lembaga Bale Literasi, 2025)
Low learning motivation is one of the main obstacles in English language learning in vocational schools, which has an impact on the suboptimal academic results of students. This study aims to determine the effect of applying group discussion and video-based learning methods on students' interest and learning outcomes in English at SMKN 1 Robatal. Using a quasi-experimental approach with a pretest-posttest control group design, this study involved learning outcome tests and learning interest questionnaires as instruments, which were analyzed using the Mann-Whitney test, ANOVA, and Spearman's rho correlation. The results showed that the experimental group obtained higher average scores than the control group, with a significant difference in learning interest (p = 0.006). After controlling for pretest scores, the posttest scores of the experimental group increased by 5.442 points and showed a significant difference (F = 15.766; p = 0.000) with a large effect size (partial eta squared = 0.360). In addition, a strong positive correlation was found between learning interest and learning outcomes (r = 0.504; p = 0.004). These findings confirm that the digital media-based collaborative learning model is relevant to the demands of the 21st century, although the generalization of the results is still limited to one school, so further research is needed on various subjects, education levels, and the integration of other interactive technologies.